Enhancing Innovative Work Behavior through Proactive Personality, Psychological Capital, Perceived Organizational Support, and Knowledge Sharing - Rika Puspitasari; Fatmah Bagis (Bulletin of Science Education, 2025)
This study examines the influence of proactive personality, psychological capital, and perceived organizational support on innovative work behavior, with knowledge sharing as a mediating variable. Mediation testing focuses on the relationship between perceived organizational support and innovative work behavior to understand the social mechanisms that drive employee innovative behavior. The research method uses a quantitative approach with a purposive sampling technique with a minimum working time of 1 year as the criteria, the population in this study was 315 and the sample used in the analysis was 190 employees from three hotels in Purwokerto. Data were collected through a questionnaire with a 5 point likert scale, then data analysis was performed using Structural Equation Modeling Partial Least Squares (SEM-PLS). the result showed that proactive personality and psychological capital had no effect on innovative work behavior, while perceived organizational support and knowledge sharing had a positive and significant effect on innovative work behavior. Furthermore, the result of the mediation test demonstrated that only knowledge sharing significantly mediated the relationship between perceived organizational support and innovative work behavior. This finding confirm that, in addition to individual factors, sosial and work environment factors such as organizational support and a culture of knowledge sharing are important in fostering innovatiion in the evolving hospitality workplace